2007
DOI: 10.4049/jimmunol.178.3.1415
|View full text |Cite
|
Sign up to set email alerts
|

Improved Outcomes in NOD Mice Treated with a Novel Th2 Cytokine-Biasing NKT Cell Activator

Abstract: Activation of CD1d-restricted invariant NKT (iNKT) cells by α-galactosylceramide (αGalCer) significantly suppresses development of diabetes in NOD mice. The mechanisms of this protective effect are complex, involving both Th1 and Th2 cytokines and a network of regulatory cells including tolerogenic dendritic cells. In the current study, we evaluated a newly described synthetic αGalCer analog (C20:2) that elicits a Th2-biased cytokine response for its impact on disease progression and immunopathology in NOD mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
102
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(120 citation statements)
references
References 40 publications
16
102
2
Order By: Relevance
“…A similar protection was observed after specific iNKT cell stimulation with exogenous ligands, a-galactosylceramide (a-GalCer) and its analogues [8][9][10][11]. Early reports suggested that iNKT cell protection was associated with the induction of a Th2 response to islet autoantigens [8,[10][11][12]. However, following studies using the transfer of anti-islet T cells showed that iNKT cells inhibit the differentiation of these auto-reactive T cells into effector cells during their priming in pancreatic lymph nodes (PLNs) [13,14].…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…A similar protection was observed after specific iNKT cell stimulation with exogenous ligands, a-galactosylceramide (a-GalCer) and its analogues [8][9][10][11]. Early reports suggested that iNKT cell protection was associated with the induction of a Th2 response to islet autoantigens [8,[10][11][12]. However, following studies using the transfer of anti-islet T cells showed that iNKT cells inhibit the differentiation of these auto-reactive T cells into effector cells during their priming in pancreatic lymph nodes (PLNs) [13,14].…”
Section: Introductionsupporting
confidence: 55%
“…iNKT cells are reduced in number in diabetes-prone NOD mice [4,5], and increasing the number of iNKT cells by adoptive transfer [6,7] or via the introduction of a Va14-Ja18 transgene, reduces significantly the progression of the disease [6]. A similar protection was observed after specific iNKT cell stimulation with exogenous ligands, a-galactosylceramide (a-GalCer) and its analogues [8][9][10][11]. Early reports suggested that iNKT cell protection was associated with the induction of a Th2 response to islet autoantigens [8,[10][11][12].…”
Section: Introductionmentioning
confidence: 78%
“…Schmieg et al observed that the C-glycoside analog of α-GalCer (α-C-GalCer) induced an immune response more skewed toward Th1 (IFN-γ) cytokines and was even more effective against B16 melanoma metastasis, further supporting the widely held belief that IFN-γ induction is a key factor for generating antitumor immunity (18). Other studies have characterized the functional activity of analogs of α-GalCer that induce more Th2 cytokine production, such as C20:2 and OCH (15,16,21,22).…”
Section: Introductionmentioning
confidence: 86%
“…Factors regulating this polarization of iNKT cells may include, but are not exclusive to, strength of TCR signal (33,34), costimulation (35), or functionally distinct iNKT subsets (36,37). Activating stimuli-inducing IFN-g and other Th1 cytokine production by iNKT cells generally leads to infection clearance and antitumor activity (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%